2020
DOI: 10.17576/gema-2020-2004-02
|View full text |Cite
|
Sign up to set email alerts
|

Processing of a Multi-representational Science Passage by ESL Learners

Abstract: Verbal input is integral and is the core component in any language learning materials. As such, despite the incorporation of non-verbal input to facilitate language learning, language learners, more often than not, give attention more to the verbal components as opposed to the non-verbal ones. This paper reports on a study undertaken to examine 28 ESL undergraduates' eye fixations when reading a science passage in English with an accompanying diagram. The data collection involves two stages. The first stage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It will improve the students' repertoire of skills and critical thinking while dealing with complicated multimodal texts (Yi & Choi, 2015). Mohd Jaafar and Thang (2020) found that the use of multiple representations (especially text and graphics) could improve students' comprehension when reading a text.…”
Section: Interaction With Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will improve the students' repertoire of skills and critical thinking while dealing with complicated multimodal texts (Yi & Choi, 2015). Mohd Jaafar and Thang (2020) found that the use of multiple representations (especially text and graphics) could improve students' comprehension when reading a text.…”
Section: Interaction With Objectsmentioning
confidence: 99%
“…Snow White in the dormitory The king on his throne When another representation, a picture for instance, is included in addition to the verbal input (linguistic mode), it makes the contents more comprehensible (Mohd Jaafar & Thang, 2020). When the drama was performed in a digital form, the visual mode could be enhanced through colour, layout, style, size and perspective.…”
Section: The Prince In the Forest Merida In The Palacementioning
confidence: 99%
“…A means to attract such readers' attention back to the main body hence might be necessary. The readers might need cues such as deictic expressions (e.g., This word can be found in line 2) or colour-coding (see Figure 5) to guide their attention from the glossary area back to the main body and encourage integration of information (Jaafar & Thang, 2020). Another alternative is to have the glosses placed on the left or right margin of the main body, in line with the paragraph, instead of at the bottom.…”
Section: The Relationship Between Processing Of Glosses and Comprehen...mentioning
confidence: 99%